2010
DOI: 10.4312/dp.37.20
|View full text |Cite
|
Sign up to set email alerts
|

Neolithic anthropocentrism: the principles of imagery and symbolic manifestation of corporeality in the Balkans

Abstract: The numerous archeological studies in the Balkans have provided a significant quantity of Neolithic ceramic objects modeled in the form of the human body. Some of these anthropomorphic artifacts were common to a particular region, or certain Neolithic phases, thus indicating their area of distribution, as well as chronological determination. Beside these elementary features, figurines and other types of anthropomorphic objects go much further than stratigraphical and regional classification, and signify a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In later prehistoric periods, adult individuals have frequently been found buried in this way. This ritual practice asserts more the symbolic aspects of burial, as well as the implementation of embodiment and anthropomorphism within material culture (Naumov, 2010a(Naumov, , 2013. The production of anthropomorphic vessels, models of houses, and models of ovens with human features was also associated with intramural burials.…”
Section: Preferred Burialsmentioning
confidence: 98%
See 1 more Smart Citation
“…In later prehistoric periods, adult individuals have frequently been found buried in this way. This ritual practice asserts more the symbolic aspects of burial, as well as the implementation of embodiment and anthropomorphism within material culture (Naumov, 2010a(Naumov, , 2013. The production of anthropomorphic vessels, models of houses, and models of ovens with human features was also associated with intramural burials.…”
Section: Preferred Burialsmentioning
confidence: 98%
“…In order to do so, burial locations, sex and age of individuals, miniaturism, and hybridism are analysed. Previous examination of these categories has suggested that Neolithic communities shared the concept of anthropomorphism, which employs the human body as the main metaphor for complex social and symbolic processes (Naumov, 2010a). A preference for particular genders and mediums of human representation was observed for the majority of Neolithic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these social features, the pottery also had a significant role in symbolic processes and therefore the painted patterns comprised of semiotic components, but some had anthropomorphic features, with the vessel from Vršnik being one of few (Naumov 2008(Naumov , 2015. In terms of symbolic objects, Neolithic societies modeled a number of anthropomorphic and zoomorphic figurines, but also house models and stamps with human and animal representations (Sanev 2006;Chausidis 2010;Naumov 2010). Regarding rituals, intramural burials were also practiced within the settlements with an apparent preference for infants, children and women buried next to or below the dwellings (Naumov 2014).…”
Section: Background -The Neolithic Of North Macedoniamentioning
confidence: 99%
“…Indeed, based on variations in the imagery of figurines, some scholars argue that they represent different life stages, from childhood to maturity and death. Alternatively, based on a combination of patterns of raw material use, stylisation techniques and breakage and deposition patterns, some researchers believe their use was connected to individuals and groups in ever more complex ways (Chapman 2000;Budja 2003;Nanoglou 2006;2009;Voigt 2007;Naumov 2009;Atakuman 2015).…”
Section: Fig 2 Neolithic Figurines As Potential Predecessors Of Thementioning
confidence: 99%